ANALISIS STRATEGI PEMASARAN GLOBAL TERHADAP PRODUK REVOLLUZIO (Studi Kasus pada PT. UNILEVER) - Suhairi, Suhairi; Mahfadillah, Aninda; Sahputri, Andriani; Suci, Indriani; Marivi, Idham (Bussman Journal : Indonesian Journal of Business and Management, 2023)
PT. Unilever is a company that produces food, beverages, hygiene and personal care products. Based on what researchers have done, Revolluzio is an e-business innovation that implements digital marketing automation. The aim of this study is to analyze the global marketing strategy for revolluzio products at PT. Unilever. This research is a type of descriptive research with a qualitative approach. This method is used because the problem under study is uncertain and temporary and can continue to grow. Furthermore, from the results of the analysis it is known that PT. Unilever implements a segmentation strategy as seen in the presentation of data which shows that PT Unilever Indonesia offers categories for various market segments and based on the segmentation described by the company, PT Unilever Indonesia in carrying out the international marketing of Revoluzio products applies product targeting tactics. target businesses